Transgenic Overexpression of Galectin-3 in Pancreatic β Cells Attenuates Hyperglycemia in Mice: Synergistic Antidiabetic Effect With Exogenous IL-33 - Jovicic, Nemanja; Petrovic, Ivica; Pejnovic, Nada; Ljujic, Biljana; Miletic Kovacevic, Marina; Pavlovic, Sladjana; Jeftic, Ilija; Djukic, Aleksandar; Srejovic, Ivan; Jakovljevic, Vladimir; Lukic, Miodrag L (Frontiers in Pharmacology, 2021)
Galectin-3 (Gal-3) has diverse roles in inflammatory and autoimmune diseases. There is evidence that Gal-3 plays a role in both, type 1 and type 2 diabetes. While the role of Gal-3 expression in immune cells invading the pancreatic islets in an experimental model of type 1 diabetes mellitus has been already studied, the importance of the overexpression of Gal-3 in the target β cells is not defined. Therefore, we used multiple low doses of streptozotocin (MLD-STZ) induced diabetes in C57Bl/6 mice to analyze the effect of transgenic (TG) overexpression of Gal-3 in β cells. Our results demonstrated that the overexpression of Gal-3 protected β cells from apoptosis and attenuated MLD-STZ induced hyperglycemia, glycosuria and ketonuria. The cellular analysis of pancreata and draining lymph nodes showed that Gal- 3 overexpression significantly decreased the number of pro-inflammatory cells without affecting the presence of T regulatory cells. As the application of exogenous interleukin 33 (IL-33) given from the beginning of MLD-STZ diabetes induction, attenuates the development of disease, by increasing the presence of regulatory FoxP3+ ST2+ cells, we evaluated the potential synergistic effect of the exogenous IL-33 and TG overexpression of Gal-3 in β cells at the later stage of diabetogenesis. The addition of IL-33 potentiated survival of β cells and attenuated diabetes even when administered later, after the onset of hyperglycemia (12-18 days), suggesting that protection from apoptosis and immunoregulation by IL-33 may attenuate type 1 diabetes.